Lumbricus rubellus earthworm as an antibacterial: A systematic review - Meutia Sara, Faridha Ilyas, Kartini Hasballah, Nurjannah Nurjannah, Harapan Harapan, Mudatsir Mudatsir (Journal of Applied Pharmaceutical Science, 2023)
Earthworms, Lumbricus rubellus, have a long history of medicinal use as adjuvant therapy or alternative medicine in a range of diseases including typhoid fever, infection of Staphylococcus, and dermatitis. The anti-bacterial effect of L. rubellus has been proven in many scientific studies, and some of the traditional applications of earthworms as a home remedy have been confirmed in humans. In this systematic review, we summarized the current evidence on the antimicrobial effects of L. rubellus against bacteria. Electronic databases including Science Direct, Wiley Online Library, Academic Search Complete, PubMed, Directory of Open Access Journal, Cochrane Library, and Indonesian Publication Index were searched for relevant studies published until October 2022, as well as direct contact with specific researchers reporting the effect of L. rubellus as an antibacterial. This review identified 17 studies that met the inclusion criteria. Fifteen studies show the antibacterial effect of L. rubellus has broad-spectrum antimicrobial peptides against Gram-negative and positive bacteria. The findings suggest that L. rubellus can be used as an alternative to antibiotics. Further high-quality clinical trials should be conducted to provide information about the long-term effectiveness and ability of antibacterial agents of L. rubellus.
Keywords: Antibacterial, earthworm, Gram-negative bacteria, Gram-positive bacteria, Lumbricus rubellus